Green Lantern. 2, The day the stars fell - Morrison, Grant (Green Lantern ;, 2019)
"The twists and turns continue as Grant Morrison shakes thing up to a whole new level! Hal Jordan has always believed in upholding the law. But after recent events he may be forced to break his own code in order to protect the universe itself! One thing is for sure. Outer space's best cop drama series continues, and Hal Jordan's world will never be the same!"--